E-Numeracy: Mobile Application of The Numeracy Understanding Model For Primary School - Ali, Siti Rahaimah Binti; Zaini, Syaza Hazwani Binti; Ahmad, Hishamuddin Bin; Mukhtar, Farah Binti (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The purpose of this study is to examine the use of e-Numeracy: Mobile Application of the Numeracy Understanding Model among primary school students. Through e-Numeration, it allows students to solve numerical problems in their respective smart devices and find out the solution for each question. This learning method supports the concept of 21st century learning and facilitates self-learning as well as fun learning. This e-Numeration can be accessed via a tablet or any digital device by using the bar code provided. The app is easy and mobile and can be accessed anywhere. Six Year Four students were selected for this study. They were chosen based on their monthly Mathematics test results. There were two students per level; good, average and weak. For data collection, this study applies qualitative design using interview methods. The result indicated that only four respondents were able to solve all the learning activities at the application level that involved concepts and facts of mathematics, procedures for selection and definition and giving reasons. Two respondents were at the level of knowledge acquisition. This level involved elaborating basic facts, defining and formulating operations that were used in the learning activities. In conclusion, through the e-Numeracy application, student is able to recognize his numeracy level of comprehension and the student can identify their error directly as well as the students enjoyed using this application. This study also indicates that the necessity to increase the level of numeracy understanding for students at elementary level.